Replacing Face-to-Face Tutorials by Synchronous Online Technologies: Challenges and pedagogical implications - Ng, Kwok Chi (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2007)
This paper reports on a study which investigates the implementation of a synchronous e-learning system (Interwise) for online tutorials on an information technology related course offered by the Open University of Hong Kong (OUHK). It examines a set of interview data related to students’ and tutors’ views on the use of the system. Issues concerning students’ participation in online tutorials, opportunities for interaction in using the system, and tutors’ roles in real-time conferences are discussed. The findings suggest that both the students and tutors are positive about the use of Interwise for online tutorials in general. Some students, however, indicate dissatisfaction with the one-way communication and teacher-control functionalities of the system. The results also indicate that the tutors are concerned about the workload involved in using Interwise in terms of managing the functionalities of the system and the different learning tasks. Implications are then drawn for supporting synchronous online learning both in the OUHK and a wider academic context.